BUDAYA K-POP DAN KEBIASAAN MAHASISWA DI ERA DIGITAL - Nasri Indra Padang; Najamuddin Najamuddin; Supriadi Torro; Firdaus W Suhaeb (Universitas Negeri Makassar, 2024)
The objectives of this research are to examine (1) the factors in driving students' interest in K-Pop culture; and (2) the impact of K-pop culture on the students’ habits in Universitas Negeri Makassar. This research employed a descriptive analysis qualitative research method. There were 10 informants in collecting the data by employing a purposive sampling technique with the criteria students who like to upload photos or videos related to K-Pop or use K-Pop idol profiles on social media, use K-Pop symbols, and have a K-Pop style appearance. Data collection was conducted by employing observation, interviews, and documentation. The data validity technique employed time triangulation, namely assessing the credibility of the data by checking the data obtained repeatedly at different times. Data analysis techniques were conducted by condensing the data, presenting the data and drawing conclusions. The results of the research reveal that (1) the factors in driving students' interest in K-Pop culture can be seen from (a) social media factors; (b) self-expression factor; and (c) peer and family factors; (2) the impact of K-Pop culture on the students’ habits in Universitas Negeri Makassar based on the positive impacts are as follows: (a) increasing networks to strengthen solidarity; (b) self-motivation to learn foreign languages and develop talents. Meanwhile, the negative impacts can be seen from (a) difficulty in managing the time; (b) wasteful; and (c) exclusive and selective in socializing.